Impact of exercise on cancer: mechanistic perspectives and new insights - Feng, Ye; Feng, Xingting; Wan, Renwen; Luo, Zhiwen; Qu, Lijun; Wang, Qing (Frontiers in Immunology, 2024)
This review critically evaluates the substantial role of exercise in enhancing cancer prevention, treatment, and patient quality of life. It conclusively demonstrates that regular physical activity not only reduces cancer risk but also significantly mitigates side effects of cancer therapies. The key findings include notable improvements in fatigue management, reduction of cachexia symptoms, and enhancement of cognitive functions. Importantly, the review elucidates the profound impact of exercise on tumor behavior, modulation of immune responses, and optimization of metabolic pathways, advocating for the integration of exercise into standard oncological care protocols. This refined abstract encourages further exploration and application of exercise as a pivotal element of cancer management.